PENERAPAN NILAI-NILAI WASATHY PADA PESERTA DIDIK MELALUI LEMBAGA PENDIDIKAN - Hasanah, Uswatun; Ramadhan, Yusfar (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The application of Wasathi values in daily life is an aspiration for every individual, aiming to create a peaceful and prosperous existence. However, implementing these values is not an easy task; it requires concrete strategies and efforts. Recent practices have shown a discrepancy with Wasathi values, such as a high level of intolerance and egoism, resulting in negative views towards those with different perspectives. This can be prevented through the application of Wasathi values, especially in educational institutions. Research results indicate that the implementation of Wasathi values, particularly in the social diversity of intensive students, can be realized through various activities and programs. Intensive students come from diverse backgrounds, but through activities like Usbu’utta’aruf, student congress programs, Gebyar Iedul Adha, as well as commemorations of Pancasila Day and the Independence Day of the Republic of Indonesia, they can form good relationships and apply Wasathi values in daily life. Values such as tawassut, tawazun, adil, tasamuh, musawah, syura, islah, aulawiyah, tatawwur wal ibtikar, tahadhdhur, wathaniyah wa muwathanah, and qudwatiyah can be implemented through these activities. This proves that the application of Wasathi values in educational institutions can create a harmonious and tolerant atmosphere among students from diverse backgrounds.